2009
DOI: 10.1002/clc.20462
|View full text |Cite
|
Sign up to set email alerts
|

Serial Analyses of C‐Reactive Protein and Myeloperoxidase in Acute Coronary Syndrome

Abstract: Background: C-reactive protein (CRP) and myeloperoxidase (MPO) are involved in the pathogenesis of atherosclerosis, mainly during periods of instabilization. This study aims to test the hypothesis that patients with acute coronary syndrome (ACS) maintain a persistent inflammatory state, and that this is associated with long-term mortality. Hypothesis: We hypothesized that serum C-reactive protein and myeloperoxidase collected at the index event and later, could add to the prognostic information in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…MPO has recently been shown to progress from stable coronary artery disease (CAD) to non-ST elevation ACS, reaching the highest levels in patients with ST-elevation acute myocardial infarction (MI) [18]. Moreover, after ACS, although plasma MPO levels decrease over time, they might remain elevated for up to 2 years of follow-up [19].…”
Section: Introductionmentioning
confidence: 99%
“…MPO has recently been shown to progress from stable coronary artery disease (CAD) to non-ST elevation ACS, reaching the highest levels in patients with ST-elevation acute myocardial infarction (MI) [18]. Moreover, after ACS, although plasma MPO levels decrease over time, they might remain elevated for up to 2 years of follow-up [19].…”
Section: Introductionmentioning
confidence: 99%
“…MPO levels before thrombolysis were significantly lower in patients with successful reperfusion. Borges et al (43) found that although the plasma MPO level decreases over time after ACS, it might remain elevated for up to 2 years of follow-up. Chang et al (44) found that high serum MPO independently predicts the risk of 30-day composite occurrence of major adverse clinical events (reinfarction, repeat PCI, Killip classification ≥3) in 128 patients with ST-segment elevation AMI undergoing primary percutaneous coronary intervention.…”
Section: Myeloperoxidase and Acute Coronary Syndromementioning
confidence: 97%
“…Preprocedural serum inflammatory markers such as C-reactive protein (CRP) level may be associated with early complications 3 and long-term prognosis 4 in patients undergoing percutaneous coronary intervention. 5 Inflammatory markers are considered a major risk factor predisposing to cardiovascular morbidity and mortality. 6 Recently, a number of studies have reported that elevated RDW levels are associated with poor prognosis in the setting of stable angina, acute coronary syndrome, coronary bypass surgery, heart failure, stroke, peripheral arterial disease, older age, and in patients with or without coronary artery disease (CAD).…”
Section: To the Editormentioning
confidence: 99%